वैदिक कालीन आयुध निर्माण तकनीकी - Manoj Kumar Rao; Ipshit Pratap Singh (Dr. Chinmay Pandya, 2015)
भारतीय संस्कृति एक हाथ में शस्त्र तथा दूसरे हाथ में शास्त्र का संदेश देती है। वैदिक काल मे तत्कालीन ऋषि मुनियों ने दुष्टों के दमन हेतु आयुध निर्माण पद्धति को विकसित किया था। मध्यकाल और आधुनिक काल में भारत में रही विदेशी ताक़तों ने आयुध निर्माण के क्षेत्र में परनिर्भरता के अवगुण को विकसित किया। भारतीय संस्कृति में सदैव 'बहुजन हिताय एवं बहुजन सुखाय' का सिद्धांत विद्यमान रहा है किंतु इसके साथ ही साथ प्रत्येक काल में इस सिद्धांत के विपरीत स्वभाव वाले लोग भी पाये गये हैं जो पर पीड़ा एवं पर अधिकार में सुख का अनुभव करते हैं। ऐसे लोगों से आत्मरक्षा एवं लोक रक्षा हेतु आयुधों की आवश्यकता पड़ती है। वैदिक ग्रंथों में अनेकों आयुधों का उल्लेख मिलता है जिनका प्रयोग वैदिक देवताओं एवं आर्य योद्धाओं द्वारा सदैव लोक कल्याण में किया गया। उन आयुधों की निर्माण तकनीकी साधारण थी किंतु उनकी शक्ति असीमित थी, क्योंकि उन आयुधों का संचालन मंत्र शक्ति पर आधृत था जिन्हें वैदिक ऋषियों एवं देवताओं ने अपनी तप शक्ति से लोक हित को ध्यान में रखकर निर्मित किया था। प्रस्तुत शोध पत्र में वैदिक कालीन उन्हीं आयुधों के प्रकार एवं निर्माण तकनीकी के विषय में उल्लेख किया गया है। प्रस्तुत शोध पत्र भारत के स्वर्णिम अतीत की शानदार उपलब्धियों को याद कर आयुध निर्माण के क्षेत्र में आत्मनिर्भरता को प्रेरित करने का प्रयास है। निःसंदेह आज हमारे पास संसाधनों का अभाव नहीं है बस आवश्यकता सृजनात्मक आत्मनिर्भरता को प्राप्त करने की है। Indian culture gives the message of weapons in one hand and scripture in the other hand. In the Vedic period, the immediate saint- sages developed an ordnance manufacturing system to get rid of evil creatures. The foreign forces in India during medieval and modern times developed a defect of dependence in the field of armament manufacturing. The principle of 'Bahujan Hitay and Bahujan Sukhaya' has always existed in the Indian culture, but at the same time people of opposite nature of this principle have been found in every era, who enjoy the pain of others. Armaments are required for self-defense and public safety from such people. Numerous armaments are mentioned in the Vedic texts, which were always used in the public welfare by the Vedic gods and Arya warriors. The construction of those armaments was technically simple but their power was unlimited, as the operation of those armaments was based on the mantra power, which the Vedic rishis and deities had created with their tenacity power keeping in mind the public interest. In the presented paper , the typology and construction technology of the same ordnance across the Vedic period has been mentioned. The presented  research paper is an attempt to inspire self-reliance in the field of armament by remembering the glorious achievements of India's golden past. Of course today we do not lack resources but there is only the need to achieve creative self-reliance.